Visible cities - Wall, Kathleen, 1950- (Brave & brilliant series ;, 2018)
"Visible Cities prompts readers to reconsider their relationship to the landscapes of cities. Poems explore streets in cities all over the world, while the photographs find beauty in back lanes, observe people taking their coffee breaks, capture people playing with a work of public art or pulling a ladder onto the roof of a downtown building. The language of the poems creates a poetic style that expresses the challenges and joys of living in cities. The photographs come from all over the world--Regina, Saskatoon, Chicago, New York, Paris, and Venice."--